2012
DOI: 10.1542/peds.2011-2290
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Uptake of Infant Male Circumcision for HIV Prevention in Western Kenya

Abstract: Fathers are important in the IMC decision-making process. Fathers, as well as mothers, should be targeted for optimal scale-up of IMC services. Circumcision programs should offer services for males of all ages, as male circumcision at some age is highly acceptable to both men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 30 publications
5
37
0
Order By: Relevance
“…These findings are consistent with those from other settings [2730]. A study conducted in Mysore, India also found that the father has the final say in whether the infant is circumcised or not [27].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are consistent with those from other settings [2730]. A study conducted in Mysore, India also found that the father has the final say in whether the infant is circumcised or not [27].…”
Section: Discussionsupporting
confidence: 89%
“…A study conducted in Mysore, India also found that the father has the final say in whether the infant is circumcised or not [27]. Within sub-Saharan Africa, the findings are consistent with those from Western Kenya and Zambia [28, 30]. In the Kenyan study, fathers of babies who had undergone EIMC were the primary decision makers in most instances, according to interviews with mothers and fathers [30].…”
Section: Discussionmentioning
confidence: 64%
“…It is possible that even men who do not accept circumcision for themselves (i.e., because of fear of pain or lost income after the procedure) will still desire the procedure for their sons, whereas the mother's support of EIMC may be more greatly affected by the circumcision status of the father. Previous research in sub Saharan Africa and elsewhere indicates circumcision status of the father is associated with maternal desire for the procedure ( Ref 13,15,32]. Given just twelve percent of mothers had talked with her partner about EIMC, it is possible that, in the absence of discussion, mothers assume an uncircumcised father will not desire circumcision for his son.…”
Section: Discussionmentioning
confidence: 98%
“…After a ''catch-up'' period of circumcising adolescent and adult males who are at highest risk of acquiring HIV in the short term, several governments including the Government of Kenya, intend to scaleup EIMC for cost-efficient HIV prevention ( Ref 11]. EIMC studies and/or service provision have begun in Botswana, Kenya, Lesotho, Swaziland, Uganda, Zambia and Zimbabwe ( Ref 8,[12][13][14][15][16]. Previous acceptability studies have indicated several common barriers to EIMC services in east and Southern Africa including: fear of pain, bleeding, death and other adverse events associated with the procedure, and cultural opposition to EIMC ( Ref 17].…”
Section: Introductionmentioning
confidence: 99%
“…However in Europe it is rarely performed [12]. The notable advantages of circumcision include: reduction in early childhood urinary tract infections, which is also noted in adult men [1317], reduction of HIV transmission by almost 60 % [1821], and reduction in the incidence of penile cancer [2224]. Ghana’s circumcision rate is estimated to be on the high side as the majority of ethnic groups and religions identify circumcision as an appropriate religious or cultural practice for males to undergo [7].…”
Section: Discussionmentioning
confidence: 99%